(NuGLENOSNOSTX SEWERNYH PREDGORIJ gINDUKU[A (B/s - (NaNDROSOW(B, (Nb(B.(Nn(B.s; (NkOL^ANOW(B, (Nw(B.(Np(B.s; (NkULAKOW(B, (Nw(B.(Nw(B.s; (NmATWEEW(B, (Na(B.(Nk(B.s; (NlABORATORIQ OSADO^NYH POLEZNYH ISKOPAEMYH an sssrs ((NmOSKWA (B:s (NnAUKA(B,s, 1977)
(NbIBLIOGR(B. 29s
Keywords: (NgORNYE PORODYs